DEVELOPING CRITICAL THINKING IN THE INFORMATION SOCIETY (Web of Humanities: Journal of Social Science and Humanitarian Research, 2026)
Personal development is no longer measured by the physical accumulation of information, but by the ability to extract necessary, reliable, and useful information from it. In an information-saturated environment, people are under dual pressure: on the one hand, opportunities for acquiring knowledge are expanding, while on the other, manipulative technologies and fake news limit a person's right to make independent decisions. Therefore, media literacy is becoming a prerequisite for personal development. It requires critical thinking and a critical approach to perceiving each piece of information.